Animal source food social and behavior change communication intervention among Girinka livestock transfer beneficiaries in Rwanda: A cluster randomized evaluation - Flax, Valerie L.; Ouma, Emily A.; Izerimana, Lambert; Schreiner, M.-A.; Brower, A.O.; Niyonzima, E.; Ufitinema, A.; Uwineza, A. (Johns Hopkins School Bloomberg School of Public Health, Center for Communication Programs, 2021)
Animal source foods (ASFs), including cow's milk, contain essential nutrients and contribute to a healthy diet, but frequency of intake is low among children in low- and middle-income countries. We hypothesized that an ASF social and behavior change communication (SBCC) intervention implemented by community health workers (CHWs) would increase child milk consumption and dietary diversity in households that received a cow from the Government of Rwanda's Girinka livestock transfer program. We tested the 9-month SBCC intervention among children aged 12-29 months at baseline in administrative cells randomly assigned to the intervention or control. Most mothers in the intervention group were exposed to CHWs' home visits (90.7%) or community-level activities (82.8%). At endline, more mothers in the intervention group compared with the control group knew that cow's milk was an ASF (90.1% vs. 81.7%, P=.03) and could be introduced to children at 12 months (41.7% vs. 18.7%, P<.001). More mothers in the intervention group compared with the control group knew they should feed their children ASFs (76.2% vs. 62.1%, P=.01) and give them 1 cup of cow's milk per day (20.6% vs. 7.8%, P<.001). Children's consumption of fresh cow's milk 2 or more times per week increased in the intervention group, although not significantly (8.0 percentage points, P=.17); minimum dietary diversity was unchanged. Children in the intervention group had increased odds of consuming cow's milk 2 or more times per week if their mothers recalled hearing that children should drink 1 cup of cow's milk per day during a CHW's home visit [odds ratio (OR) 2.1, 95% confidence interval (CI) (1.1, 3.9)] or a community activity [OR 2.0, 95% CI (1.2, 3.5)]. Approximately half of the children had no milk during the past week because their households produced too little or sold what was produced. In poor households receiving a livestock transfer, strategies to further tailor SBCC and increase cow's milk production may be needed to achieve larger increases in children's frequency of milk consumption.